Validity and Reliability of the Thai Version of the Barthel Index Self-Report (BI-SR-TH) for People with Spinal Cord Injury - Tongprasert, Siam; Mekkij, Sirinna; Kammuang-lue, Pratchayapon; Wongpakaran, Tinakon (Biomedical Sciences and Clinical Medicine, 2025)
Objective This study aimed to cross-culturally translate and evaluate the psychometric properties of the Thai version of the Barthel Index Self-Report (BI-SR-TH) for Thai people with spinal cord injury (SCI). Methods A descriptive cross-sectional validation and reliability study was conducted at the Maharaj Nakorn Chiang Mai Hospital, involving 109 Thai people aged 18 or older with either traumatic or non-traumatic SCI. The English postal version of the Barthel Index was translated into Thai following standard cross-cultural procedures, including forward and backward translation. Participants completed both the BI-SR-TH and the Thai EuroQoL (EQ-5D-5L) questionnaires via self-report and clinician assessment using the Barthel Index. The BI-SR-TH was re-administered to the participants one week later. Psychometric evaluation included assessments of internal consistency (Cronbach’s alpha), concurrent validity (Spearman’s correlation with clinician-rated BI), construct validity (convergent and discriminant validity assessed by correlations with relevant and distinct EQ-5D-5L domains), and test-retest reliability (intraclass correlation coefficient, ICC). The agreement between the BI-SR-TH and BI scores was assessed using ICC and the Bland-Altmand Altman analysis. Item-level agreement was assessed using the Kappa statistic. Results The BI-SR-TH demonstrated good internal consistency (Cronbach’s alpha = 0.836) and excellent concurrent validity with a clinician-rated BI (r = 0.884). In terms of construct validity, the BI-SR-TH showed strong negative correlations with relevant EQ-5D-5L domains, e.g., mobility, self-care, and usual activities (r = –0.67 to –0.81, p < 0.01), demonstrating convergent validity. In contrast, correlations with unrelated domains such as anxiety and pain were weak or nonsignificant, indicating discriminant validity. The total score agreement between BI-SR-TH and the clinician BI was high (ICC = 0.916), and Bland-Altman analysis indicated a small mean difference. Most BI-SR-TH items showed good agreement with clinician ratings (Kappa 0.61–0.72) with the exception of the bowels and bladder items which showed only fair agreement (Kappa = 0.34 and 0.35, respectively). Test-retest reliability was also high (ICC = 0.924). Conclusions The BI-SR-TH is a valid and reliable tool for assessing functional independence in Thai people with SCI. However, the bowels and bladder items require further refinement for this population